Penerapan Metode Multi Attribute Utility Theory (MAUT) dalam Memberikan Rekomendasi Pemenang Lomba MTQ - Lusia Lamalewa; Lilik Sumaryanti (JUSIFO : Jurnal Sistem Informasi, 2021)
Musabaqah Tilawatil Qur'an is a competition in the field of syiar ’s content. The decision of the winners in MTQ competition was determined by the judges, especially in Merauke district, is currently carried out by the judges of each field, with the calculation of the value based on predetermined criteria. However, in its assessment, it has not applied priority to the criteria used to determine the winner. The results of the assessment given have not used data analysis methods that can be used to process assessment data into information that will support decision making in determining the winner of the competition. In order to reduce subjectivity in the assessment of participants, a decision support system is needed that has implemented a decision-making method. This study aims to build a decision support system using the Multi Attribute Utility Theory (MAUT) method. The results on the implementation of this method in a decision support system using an accuracy test indicated an accuracy of 95.6%. The accuracy value indicates that the MAUT method is an accurate data analysis method in analyzing the assessment data for determining the winner of the MTQ competition.